BEBAN RESTITUSI PELAKU PEMERKOSAAN MENURUT PERSPEKTIF FIKIH DAN QANUN JINAYAT - Nouvan Moulia; Putri Kemala Sari (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
Compensation for rape victims stipulated in Aceh’s Qanun No. 6/2014 concerning the Law of Jinayat has not been implemented as expected. The initiation of a victim's request and the inability of perpetrators to pay the restitution were considered as the inhibiting factors. This research tried to identify and explain: (1) the basis of Islamic jurisprudence (fiqh) regarding restitution for victims of rape, (2) a fiqh perspective regarding the provisions and procedures for restitution for victims of rape that have been regulated in Qanun Jinayat and Qanun Acara Jinayat, (3) a fiqh perspective on the obligation of the state to assist rape perpetrators who are financially unable to pay the restitution. This type of research is a literature study employing a review of the document. All data were qualitatively analyzed using methods of descriptive analysis and content analysis. The findings revealed that: (1) compensation for victims of rape from a fiqh perspective is part of the basic sentence decided by the judge along with decision of physical punishment, while according to Qanun Jinayat and Qanun Acara Jinayat, compensation is not part of the basic sentence, (2 ) according to a fiqh perspective, a rape victim has the right to receive compensation in the form of mahar misil (dowry) which is paid multiple times according to repeated rape, ursy al-bikarah, or others in accordance with the losses suffered by the victim, whereas according to Qanun Jinayat and Qanun Acara Jinayat, compensation for rape victims is an amount of money or certain assets paid for suffering, loss of property, or compensation for certain actions, (3) from a fiqh perspective, the state is obliged to help the perpetrators of rape to pay off the burden of restitution which cannot be repaid due to financial constraints by distributing for them the right of gharim from the treasury of zakat collected by baitul mal.